Conhecimento dos graduandos de fisioterapia acerca da atuação fisioterapêutica na apneia obstrutiva do sono - Santos, Emanuel Davi Simões dos (2019)
INTRODUCTION: Obstructive Sleep Apnea (OSA) is a respiratory sleep disorder considered a public health problem with direct association with heart and cerebrovascular diseases. Treatment is done with Continuous Positive Airway Pressure (CPAP) equipment, with the physiotherapist playing an important role in patient compliance. However, there is insufficient occupation of the professional in this field. It is suspected that there is a lag in the knowledge of the physiotherapist about the management of sleep breathing disorders since graduation. OBJECTIVE: To investigate the knowledge of Physiotherapy undergraduates regarding the physiotherapeutic performance of OSA patients. METHOD: cross-sectional, descriptive and quantitative study with a sample of undergraduate students from the last year of the Physical Therapy course in the city of Fortaleza through the application of an online form investigating the knowledge of OSA in the respondent's perception. RESULTS: We obtained answers from 40 undergraduates, equally distributed among public and private higher education institutions, with an average age of 24 years, most of them female (87.5%). Respondents were little aware of the diagnostic aspects (60%), forms of treatment (52.5%) and the role of the physiotherapist in patient compliance with CPAP therapy (52.5%). CONCLUSIONS: The undergraduates were uncertain as to the diagnostic aspects and the forms of treatment in OSA, as well as regarding the physiotherapeutic performance in the patient's adherence to CPAP therapy. It was observed that most receive insufficient information about OSA during the undergraduate course, feeling little encouraged to seek evidence about the theme.